Injury incidence rates and profiles in elite taekwondo during competition and training - Geßlein, M.; Rüther, J.; Bail, H. J.; Schuster, P.; Krutsch, W.; Wolpert, A. K. (International Journal of Sports Medicine, 2020)
This study aimed to investigate exposure adjusted injury incidence rates and profiles associated with training and competition in an elite taekwondo athlete population. 82 athletes were investigated for injuries over a period of 5 years. Individual fight time exposure for training and competition was recorded. The type and location of the injuries were classified and exposure-adjusted injury incidence rates (IIR) were calculated per 1000 h for training and competition. 66 athletes with a mean age of 19.3±4.2 years and 172 injuries were included in the final data assessment. The exposure adjusted IIR was significantly higher during competition (p<0.001) with a rate ratio of 6.33 (95% CI 4.58-8.69). Ankle and foot region as well as hand and wrist were most affected with significant higher IIR in competition (p<0.001). Joint injuries, fractures, and bruising occurred the most. Fractures occurred mainly to the hand and wrist region. Future investigations should focus on exposure adjusted injury data including analyses of the detailed mechanism leading to especially severe injuries to improve specific injury prevention in competition and promote evolution of protective gear